Investigation of aerodynamic shielding between traffic control attachments and mast-arm support structures. (15th December 2019) - DeMello, Neandro; Smith, Joshua; Bridge, Jennifer A.; Consolazio, Gary R.; Gurley, Kurtis
Highlights: Typical assessment of mast-arm structures neglect aerodynamic shielding. Wind tunnel tests conducted on reduced-scale representative mast-arm structures. Aerodynamic shielding is a function of attachment height to arm pole diameter. A new approach that accounts for aerodynamic shielding is proposed. Aerodynamic shielding has significant impact on attachments with small h/D ratios. Abstract: The representation of static wind loading for the assessment/design of mast-arm structures typically superimposes the wind load on each individual component (upright mast, arm pole, signs, and signals). This superposition includes portions of the upright mast and arm pole that are shielded from direct exposure to wind by signs or signals, implicitly assuming negligible aerodynamic shielding. The key objectives of this study were to experimentally investigate the presence of aerodynamic shielding, to quantify its influence on structural demands from wind-induced loading, and to propose an approach for determining design static wind loads on mast-arm structures that accounts for aerodynamic shielding. Wind tunnel tests were conducted on reduced-scale mast-arms and components which were representative of structural usage in Florida. The experiments established that reduced loading on shielded mast-arm segments does occur. A simple geometry-dependent model of wind load that accounts for the presence of aerodynamic shielding is proposed. The reduced load on the shielded pole segments is accounted for via load reduction on the shielding attachment as a proxy. The concept of an 'aerodynamic shielding factor' is introduced as the load reduction mechanism. This approach preserves the current superposition methodology used in design while also accounting for shielding effects.